2′-Modified Guanosine Analogs for the Treatment of HCV. (2nd June 2016) - Girijavallabhan, Vinay; Arasappan, Ashok; Bennett, Frank; Chen, Kevin; Dang, Qun; Huang, Ying; Kerekes, Angela; Nair, Latha; Pissarnitski, Dmitri; Verma, Vishal; Alvarez, Carmen; Chen, Ping; et al.
ABSTRACT: Novel 2′-modified guanosine nucleosides were synthesized from inexpensive starting materials in 7–10 steps via hydroazidation or hydrocyanation reactions of the corresponding 2′-olefin. The antiviral effectiveness of the guanosine nucleosides was evaluated by converting them to the corresponding 5′-O-triphosphates (compounds38–44 ) and testing their biochemical inhibitory activity against the wild-type NS5B polymerase.